Running demands in club, regional, national, and international provincial New Zealand rugby union competitions - Peter Olsen; Richard Deuchrass; Shaun Owen; Matt Lilley; James Jowsey; Michael Hamlin (Frontiers Media S.A., 2023)
The demands of national and international professional rugby union matches are well established, however, there has not been a comparative study investigating running demands in New Zealand teams playing in club (amateur), Heartland Championship (semi-professional Div 2), the Mitre 10 Cup (semi-professional Div 1) or Super Rugby (professional) competitions. This information could enable specific training and rehabilitation that programmes to be developed to meet the needs of players in the different competitions. Players wore 10 Hz GPS units during games for one rugby season to determine absolute (m) and relative (m.min−1) measures for total distance, running volume (∼≥7 km·h−1) and high intensity running (∼≥16 km·h−1). There were typically minimal differences (1-2 m.min−1) in running distance measures between amateur level front row forwards and inside backs compared to players in these positions at higher levels of competition. Therefore, amateur players in these positions may find the transition to higher competitions less challenging with respect to running load. In contrast, amateur outside backs and back row forwards may find the increased pace of higher levels of competition more challenging due to typically covering significantly less running and high intensity running distances in amateur games. Differences for half backs were more variable between the levels of competition. Based on our results, it cannot be assumed that amateur rugby has lower running demands than higher competitions or that there is a continuum of increased running demands with increasing competition levels, as some playing positions in the semi-professional (Div 2) (second lowest level of competition) team recorded the largest values for total distance, running and high intensity running. Therefore, the specificity of running demands in a position and competition need to be considered individually for each player when transitioning between competitions. The practice and perception of returning a professional player to amateur club rugby due to the belief that running loads being lower may also be flawed, as we found considerable positional variation in running demands within-and-between competitions.